Formulation and Evaluation of Herbal Anti-Sweat Roll on for Summer - Chatur Sneha Nanasaheb; Mate Vaishnavi Tukaram; Kale Pratiksha Dattu; Dhamane Kajal Surendra; Bhalke Rasika Dnyandeo; Giri Mahendra Ashok (Asian Journal of Pharmaceutical Research and Development, 2026)
The increasing preference for natural and safe cosmetic products has encouraged the development of herbal alternatives to conventional deodorants and antiperspirants. Sweating is a normal physiological process; however, the breakdown of sweat by skin microflora leads to unpleasant body odour. Synthetic antiperspirants, commonly containing aluminium salts, may reduce perspiration but are often associated with skin irritation and safety concerns on prolonged use (1,2). The present study was designed to formulate and evaluate an anti-sweat herbal roll-on using plant-based ingredients such as neem extract, aloe vera gel, alum, and essential oils known for their antimicrobial and astringent properties. The formulation was prepared by incorporating herbal extracts into a suitable aqueous base and evaluated for parameters including pH 5.8, viscosity 450 cps, spreadability 19.5g.cm/s, homogeneity was Excellent, skin irritancy was Absent,and stability was Highly Stable. The developed formulation exhibited acceptable physicochemical characteristics, maintained stability under different storage conditions, and showed no signs of irritation on application. The presence of herbal components contributed to effective control of odour-causing microorganisms. Hence, the study supports the use of herbal roll-on formulations as a safe and effective alternative to synthetic deodorants.